Growing the Productivity of Government Services - Dunleavy, Patrick (Edward Elgar Publishing, 2013)
Productivity is essentially the ratio of an organization's outputs divided by its inputs. For many years it was treated as always being static in government agencies. In fact productivity in government services should be rising rapidly as a result of digital changes and new management approaches, and it has done so in some agencies. However, Dunleavy and Carrera show for the first time how complex are the factors affecting productivity growth in government organizations - especially management practices, use of IT, organizational culture, strategic mis-decisions and political and policy churn. With government budgets under stress in many countries, this pioneering book shows academics, analysts and officials how to measure outputs and productivity in detail; how to cope with problems of quality variations; and how to achieve year-on-year, sustainable improvements in the efficiency of government services.